NanoMi: An open source electron microscope hardware and software platform. (December 2022) - Malac, Marek; Calzada, Jesus Alejandro Marin; Salomons, Mark; Homeniuk, Darren; Price, Patrick; Cloutier, Martin; Hayashida, Misa; Vick, Doug; Chen, Sean; Yakubu, Suliat; Wen, Zhengxu (Darren); Leeson, Marcus; et al.
Abstract: We outline a public license (open source) electron microscopy platform, referred to as NanoMi. NanoMi offers a modular, flexible electron microscope platform that can be utilized for a variety of applications, such as microscopy education and development of proof-of-principle experiments, and can be used to complement an existing experimental apparatus. All components are ultra-high vacuum compatible and the electron optics elements are independent from the vacuum envelope. The individual optical components are mounted on a 127 mm (5-inch) diameter half-pipe, allowing customizing of electron optics for a variety of purposes. The target capabilities include SEM, TEM, scanning TEM (STEM), and electron diffraction (ED) at up to 50 keV incident electron energy. The intended image resolution in SEM, TEM and STEM modes is ≈ 10 nm. We describe the existing components and the interfaces among components that ensure their compatibility and interchangeability. The paper provides a resource for those who consider building or utilizing their own NanoMi. Highlights: Open source electron microscope. Ultra high vacuum electron microscope. Electrostatic electron and ion optics. Custom electron beam column. Electron microscopy education.